2022
DOI: 10.1002/anie.202210242
|View full text |Cite
|
Sign up to set email alerts
|

A Deprotection‐free Method for High‐yield Synthesis of Graphdiyne Powder with In Situ Formed CuO Nanoparticles

Abstract: With a direct band gap, superior charge carrier mobility, and uniformly distributed pores, graphdiyne (GDY) has stimulated tremendous interest from the scientific community. However, its broad application is greatly limited by the complicated multistep synthesis process including complex deprotection of hexakis-[(trimethylsilyl)ethynyl]benzene (HEB-TMS) and peeling of GDY from the substrates. Here, we describe a deprotection-free strategy to prepare GDY powder by directly using HEB-TMS as the monomer. When CuC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…As far as we know, this is the first report about GDY-supported Cu 2 O material. We noticed that there were several reports about synthesis of GDY-supported Cu(0) or CuO via the similar strategy. We compared the detailed synthesis conditions in our work to those in the literature and found that the main differences were the kind of catalysts and the reaction atmosphere, thus leading to different Cu species on GDY.…”
Section: Resultsmentioning
confidence: 96%
“…As far as we know, this is the first report about GDY-supported Cu 2 O material. We noticed that there were several reports about synthesis of GDY-supported Cu(0) or CuO via the similar strategy. We compared the detailed synthesis conditions in our work to those in the literature and found that the main differences were the kind of catalysts and the reaction atmosphere, thus leading to different Cu species on GDY.…”
Section: Resultsmentioning
confidence: 96%
“…The monomer Hexakis[(trimethylsilyl)ethynyl] benzene (TMS-HEB) was prepared based on the previous report. 51 Then, the synthetic TMS-HEB and CuCl ([TMS-HEB = 5.0 g, CuCl = 0.85 g) were dissolved in N,N-dimethylformamide (DMF) solvent, and the mixture was heated at 60 °C for 24 h in air. After reaction, the product was washed with DMF, THF, and deionized water, respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The noble metal ruthenium could be replaced by earth-abundant elements as well. 51,52 For example, Nikoloudakis et al presented efficient and selective conversion from para-substituted phenyl alcohols (1a-1c) into the corresponding aldehydes (2a-2c) with a zinc porphyrin (ZnP) sensitizer (5). 47 The photosensitizer was anchored on the surface of a TiO 2 photoanode by a robust hydroxamic group and hence was able to work both in aqueous solutions and organic solvents.…”
Section: Alcohol Oxidationmentioning
confidence: 99%
“…1,2 Fixing solar energy in value-added compounds, like fuels and building-block chemicals, is a promising way to realize the storage of solar energy and has received considerable attention from the chemical community. [3][4][5][6] Developing green and efficient methods of converting solar energy into chemical energy is becoming the future trend of energy and synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%